Effect of water deficit stress on diffusive resistance, transpiration, and spikelet desiccation of rice (Oryza sativa L.) - Ekanayake, I.J.; De Datta, S.K.; Steponkus, P.L. (1993)
To understand the nature of panicle resistance to water loss, diffusive resistance, transpiration rate, and degree of tissue desiccation were studied as affected by low tissue water potentials and relative water contents (RWC) induced by water deficit stresses. A drought susceptible cultivar (IR20) and a moderately resistant cultivar (IRAT 13) were compared under moderate and severe water deficit stresses under greenhouse conditions. Irrigation was withdrawn at flowering stage. During the 10-d stress period, changes in panicle and flag leaf transpiration and white head formation (desiccated) were monitored. Using cut panicles transpiration and white head formation at different RWC levels in 11 different cultivars were also measured. In flag leaves, increased diffusive resistance and leaf rolling reduced transpirational losses from the adaxial surfaces. Leaf resistance and rolling were linearly correlated with leaf water potentials. Resistance in panicles increased with progress decline in water potentials, but the change was not as high as in leaves. Among test cultivars, diffusive resistance increased at the late flowering stage but not at the early stage when panicles were newly emerged. Increased water losses contributed to severe spikelet desiccation and white heads. A few of the upland cultivars tested, such as Kinandang Patong, IRAT 140 and IRAT 13 conserved more water and showed reduced water-deficit stress symptoms.